Impacto das estratégias de gestão sobre o crescimento de PMES: uma atualização - Foletto, Gabrielle Viegas (Universidade do Vale do Rio dos Sinos, 2020)
Small and Medium Enterprises (SMEs) are recognized for their important role in generating jobs and wealth around the world. However, despite this relevance and advances in the literature, there is little consensus on the effects of the different management strategies used by SMEs on their growth. In reality, the set of studies carried out on the subject offers conflicting and fragmented evidence. This dissonant evidence indicates the complexity of understanding how SMEs grow. Based on this problem, this research aimed to analyze how knowledge about the influence of strategic management on the growth of SMEs has advanced in recent years. To this end, the study by Dobbs and Hamilton (2007) was taken as a starting point, which synthesized decades of studies on the growth antecedents - including management strategies - of small and medium-sized firms. This research was carried out through a review of the literature published in high impact journals between the years 2008 and 2018. In terms of theoretical contributions, the analyzes of this study contribute to the systematization of the growth field of small and medium businesses. It is concluded that the strategies that favor the growth contemplate seven distinct categories. The results found are in addition to the findings of Dobbs and Hamilton (2007). Specifically, three identified categories complement the findings of these authors: Financing Strategies; People management; R&D and Innovation. In addition, four new categories of strategies were presented: Management and Planning Style; Entrepreneurial Orientation; Business model; Marketing strategies. Empirical, managerial and governmental contributions are presented at the end of this research.
Keywords: Pequenas e médias empresa; PME; Crescimento; Estratégias de gestão; Revisão da literatura; Small and medium enterprises; SME; Growth; Management strategies; Review of the literature; ACCNPQ::Ciências Sociais Aplicadas::Administração